The nanomechanical properties of non-crosslinked calcium aluminosilicate hydrate: The influences of tetrahedral Al and curing age. (September 2022) - Li, Jiaqi; Zhang, Wenxin; Sanz-Camacho, Paula; Duttine, Mathieu; Gardner, David; Carraro, Carlo; Maboudian, Roya; Huthwelker, Thomas
Abstract: Calcium aluminosilicate hydrate (C-A-S-H) is the binding phase of both blended cement-based and alkali-activated materials. The intrinsic mechanical properties of non-cross-linked C-A-S-H are important while experimentally unvalidated. Here, the properties are for the first time measured using high-pressure X-ray diffraction. The incompressibility and bulk modulus K0 of C-A-S-Hs are correlated to their nanostructure and stability using nuclear magnetic resonance and X-ray absorption spectroscopies. Al coordination in stable C-A-S-H (Al/Si = 0.1) cured for 546 days is purely tetrahedral (Al IV ), while in metastable C-A-S-H (Al/Si = 0.05) cured for only 182 days is both Al IV and pentahedral (Al V ). The stable C-A-S-H is stiffer along the a, b, c-axis with higher K0 relative to C-S-H. Short-curing-induced metastable C-A-S-H (Al/Si = 0.05) shows expanded interlayer and softer c-axis, thus lower K0 than C-S-H and the stable C-A-S-H. Our results highlight the stiffening effect of Al IV incorporation and the negative influences of insufficient curing on the nanomechanical properties of non-cross-linked C-A-S-H at Ca/Si = 1.